Nonlinear dynamics of a flexible portal frame under support excitation - De Paula, Aline Souza; Balthazar, José Manoel [UNESP]; Felix, Jorge Luis Palacios (AIP Publishing, 2012)
This paper presents a nonlinear dynamic analysis of a flexible portal frame subjected to support excitation, which is provided by an electro-dynamical shaker. The problem is reduced to a mathematical model of four degrees of freedom and the equations of motion are derived via Lagrangian formulation. The main goal of this study is to investigate the dynamic interactions between a flexible portal frame and a non-ideal support excitation. The numerical analysis shows a complex behavior of the system, which can be observed by phase spaces, Poincaŕ sections and bifurcation diagrams. © 2012 American Institute of Physics.
Keywords: Electro-dynamical shaker; flexible portal frame; nonlinear dynamics